Metodología para la estimación de la dependencia de las tasas de cambio en Colombia (2019)
This document measures the dependence of the exchange rates of the dollar and the euro with respect to the Colombian peso and its forecast. For this purpose, the copula methodology and time series were used following a GARCH model. The value at risk was established for a fictional portfolio that has investments in both dollars and euros, with varied proportions of investment in both currencies.